Ekstraksi Asam Lemak Dari Daging Buah Alpukat - Zulharmita Zulharmita; Reni Afrina; Rina Wahyuni (Jurnal Farmasi Higea, 2013)
The fatty acid content analysis of avocados pulp taken from Batusangkar (Sumatra Barat) area had researched. Avocado were  divided into 2 groups, that are group A : broaded in 3 days, group B : broaded in 5 days. Group A produced 149.274 g oils, whereas group B produced 169.598 g oils, analysis of avocado oil of group A by GC-MS showed the avocado oil components, namely acid miristat (2.44%), acid behenat (2.22%) and acid isopalmitat (10.97%), whereas the avocado oil components of group B are acid nonanoat (1.20%), acid miristat (2.80%), acid behenat (2.23%), acid palmitoleainat (7.91%), acid oleat (10.95%), acid oleat (28.69%), acid isopalmitat (4.77%).